Analisis Pengaruh Kualitas Produk dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan Pada PT Rekso Nasional Food (Mc Donald’s) Villa Mutiara Gading - Hutapea, Sharoon Calvin; Yanuari, Yayan; Surtini (Mulia Pratama, 2024)
Based on the analysis of multiple regression results, the variables product quality (XI) and service quality (X2) on customer satisfaction (Y) with a multiple regression coefficient with the result Y 2.951 0.539 0.381 from the calculation results above show that product quality and service quality on customer satisfaction has a positive influence, because each coefficient is positive, where bl 0.539 and 62-0.381, meaning that with product quality and service quality (XI and X20) customer satisfaction is 2.951. Based on calculations using the coefficient of determination (R2) approach, the percentage level of product quality and service quality variables on customer satisfaction is 0.772% This proves that the customer satisfaction variable is influenced by product quality and service quality variables by 77.2% and the remaining 22.8% is influenced by other factors or other variables that are not examined such as other factors such as competitors, price, place strategy and etc Based on the ttest hypothesis test (HI) for the product quality variable (X1), Ttable of 2.011 is obtained. The t distribution table is searched at a 5% 2 (wo- way test) with degrees of freedom (dfn-k-1) or 50-2-147, n is the number of respondents and k is the number of independent variables. So the results of partial Hypothexis testing obtained the following results, product quality has a positive and significant effect on customer satisfaction. This is indicated by the T value of 5.087 with a significant value of 0.000. Based on the hypothesis test ttest (H2) for the price variable (X2), a Ttable of 2011 is obtained. The t distribution table is searched for at a 5%: 2 (two-way test) with degrees of freedom (dfn-k-1) or 50-2-1 47, n is the number of respondents and k is the number of independent variables. So the results of partial hypothesis testing obtained the following results, service quality has a positive and significant effect on customer satisfaction. This is indicated by the T value of 3.429 with a significant value of 0.001 Based on the hypothesis test ttest (H2) for the price variable (X2), a Ttable of 2011 is obtained. The t distribution table is searched for at a 5%: 2 (two-way test) with degrees of freedom (df n-k-1) or 50-2-147, n is the number of respondents and k is the number of independent variables. So the results of partial hypothesis testing obtained the following results, service quality has a positive and significant effect on customer satisfaction. This is indicated by the T value of 3.429 with a significant value of 0.001.